2019
DOI: 10.1002/ange.201906056
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electrocatalytic N2 Reduction via Partial Anion Substitution in Titanium Oxide–Carbon Composites

Abstract: The electrochemical conversion of N 2 at ambient conditions using renewably generated electricity is an attractive approach for sustainable ammonia (NH 3 )p roduction. Considering the chemical inertness of N 2 ,r ational design of efficient and stable catalysts is required. Therefore,i nt his work, it is demonstrated that aC -doped TiO 2 /C (C-Ti x O y /C) material derived from the metal-organic framework (MOF) MIL-125(Ti) can achieve ah igh Faradaic efficiency (FE) of 17.8 %, which even surpasses most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…[7] Therefore, a series of rigorous control experiments and 15 N isotopic labeling experiment are usually required to confirm the origin of the produced NH 3 and exclude the possible ammonia contamination. In addition, to boost the performance of electrochemical NRR at ambient conditions, much efforts have been paid designing efficient catalysts, especially transition metal-based catalysts such as Au-based catalysts, [8] Fe-based catalysts, [9] Mo-based catalysts, [10] Ti-based catalysts, [11] etc. Despite encouraging advancements have been achieved during the past few years, the NRR activity and selectivity of the transition metal-based materials are still far from satisfactory mainly because the d electrons of transition metals are prone to the formation of metal-H bond for competitive HER, leading to a low NRR selectivity and low catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Therefore, a series of rigorous control experiments and 15 N isotopic labeling experiment are usually required to confirm the origin of the produced NH 3 and exclude the possible ammonia contamination. In addition, to boost the performance of electrochemical NRR at ambient conditions, much efforts have been paid designing efficient catalysts, especially transition metal-based catalysts such as Au-based catalysts, [8] Fe-based catalysts, [9] Mo-based catalysts, [10] Ti-based catalysts, [11] etc. Despite encouraging advancements have been achieved during the past few years, the NRR activity and selectivity of the transition metal-based materials are still far from satisfactory mainly because the d electrons of transition metals are prone to the formation of metal-H bond for competitive HER, leading to a low NRR selectivity and low catalytic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…C(N)-Ti bonds can still be observed in H-NTO-650, while C-NTO-650 is entirely free of C(N)-Ti bonds, indicating that C (N) atoms can occupy the oxygen vacancies generated to form the NTO/C (N) interface, which has also been reported in the related literature. [24] UV-vis absorption spectra and XPS valence band spectroscopy further confirmed the enhanced electrical conductivity. The band gap energies (E g ) of all materials were also investigated by UVvis absorption spectroscopy, and it was observed that the absorption edges of A-NTO and H-NTO had shifted to 374 and 387 nm, respectively, when compared to C-NTO (Figure S16a, Supporting Information); therefore, the E g of C-NTO, A-NTO, and H-NTO were 2.89, 2.98, and 3.05 eV, respectively (Figure S16b, Supporting Information).…”
Section: Materials Synthesis and Structural Characterizationmentioning
confidence: 61%
“…B and N co‐doped carbons with highly porous structures were synthesized with desirable NRR performance. Doped heteroatoms can successfully construct B−N bonds and possible Frustrated Lewis pairs (FLPs) from unsaturated B and N atoms, which can provide active sites for N 2 reduction …”
Section: Can Catalyst Design Alone Make Nrr a Competitive Processmentioning
confidence: 99%